PENERAPAN MODEL SOMATIC, AUDITORY, VISUALIZATION, DAN INTELECTUALLY (SAVI) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS IV - Kamaruddin Hasan; nurul mukhlisa; Ayu Lestari (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The purpose of this study was to determine: (1) The Process of Application of the SAVI Model in Social Studies Subjects for Class IV MI DDI Jabal Nur Parepare Students, (2) Social Studies Learning Outcomes for Class IV MI DDI Jabal Nur Parepare Students through the application of the SAVI Model. The approach used is a qualitative approach and the type of research used is classroom action research. This research focuses on the process and student learning outcomes. Data collection techniques used are observation, testing, and documentation. Then, analyzed using qualitative descriptive data analysis. The conclusion in this study is that by applying the SAVI model can improve social studies learning outcomes about production equipment, communication and transportation in class IV MI DDI Jabal Nur Parepare students.